Extraction temperature is a decisive factor for the properties of pectin. (March 2021) - Chen, Jianle; Cheng, Huan; Zhi, Zijian; Zhang, Hua; Linhardt, Robert J.; Zhang, Fuming; Chen, Shiguo; Ye, Xingqian
Abstract: Pectin is an important food thickener and gelling agent and also, based on its bioactivities, is becoming viewed as a healthy polysaccharide. The functional properties of pectin are related to its structure which, if raw materials are similar, is controlled by extraction conditions. In our previous study we found that pectin recovered from citrus canning processing water showed some unique structural features and properties compared to commercial citrus pectin. Thus, the mechanism of pectin extraction under different conditions including the canning process, an unusual condition for pectin extraction, was studied. The same raw material of citrus fruit segment membrane was used and the properties of the extracted pectin and the resulting residue were characterized. The unusual low extraction temperature, applied in canning, was identified as a key factor for the unique structural features of the recovered pectin. The low-temperature extraction resulted in reduced yields ( 9%, half of the commercial process), meanwhile, it limited the hydrolysis of pectin side-chains. The proportion of arabinose (Ara), one major side-chain sugar, was much higher ( 23%), than that of commercial citrus pectin, resulting in a lower proportion of galacturonic acid (GalA). Moreover, the low-temperature extracted pectin having these structural features exhibited greater apparent viscosity and higher galectin-3 binding affinity (3.87 μM). The current study suggests the mechanism of pectin extraction and supplies important information for the extraction of functionally tailored pectin. Graphical abstract: Image 1 Highlights: Extraction mechanism was proposed by analyzing both of the pectin and residue. Extraction temperature is a major factor affecting the pectin structure. Pectin extracted below 40 °C remains more neutral sugar branches as original state. Low-temperature extracted pectin exhibits higher viscosity and bioactivity.